Automata [videorecording (DVD)] - Ibáñez, Gabe, 1971-; Legarreta, Igor, 1973-; Sánchez Donate, Javier; Banderas, Antonio; Griffith, Melanie, 1957-; Sørensen, Birgitte Hjort, 1982-; Forster, Robert, 1942-2019; McDermott, Dylan; McInnerny, Tim ([publisher not identified], 2014)
In a future where Earth's ecosystem verges on collapse, man-made robots roam the city to protect dwindling human life. When a robot overrides a key protocol put in place to protect human life, ROC Robotics insurance agent Jacq Vaucan is assigned to locate the source of the manipulation and eliminate the threat. What he discovers leads Vaucan, ROC Robotics and the police into a battle with profound consequences for the future of humanity.